2021
DOI: 10.1002/lary.29805
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Human Papillomavirus Awareness and the Role of Oropharyngeal Squamous Cell Carcinoma Education on Improving Intention to Vaccinate

Abstract: Objectives/Hypothesis: The current state of the U.S. public's knowledge of the relationship between human papillomavirus (HPV) and HPV vaccinations to oropharyngeal squamous cell carcinoma (OPSCC) is unknown. Our objective was to 1) assess the general population's knowledge of human papillomavirus (HPV) and willingness to vaccinate, and 2) assess whether targeted education on HPV-related OPSCC can change intentions to vaccinate.Study Design: Online cross-sectional survey.Methods: An online, cross-sectional sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
(43 reference statements)
2
7
0
Order By: Relevance
“…27 This study also revealed 36% of patients selected an Otolaryngologist as their ideal way to be educated on HPV's role in OPSCC. 27 Otolaryngology practices, including those with an imbedded Audiology practice who see a significant number of eligible patients, are a unique position to speak to HPV related diseases, see a large volume of both adolescent male and female patients who are due for HPV POCV, may be able to give a strong recommendation for vaccination, and facilitate its administration to decreased MO and increase community vaccination rates. One consideration for Oto-HNS providers is whether adding vaccination capabilities would place a significant burden on the clinic to make vaccination fiscally or logistically unviable.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…27 This study also revealed 36% of patients selected an Otolaryngologist as their ideal way to be educated on HPV's role in OPSCC. 27 Otolaryngology practices, including those with an imbedded Audiology practice who see a significant number of eligible patients, are a unique position to speak to HPV related diseases, see a large volume of both adolescent male and female patients who are due for HPV POCV, may be able to give a strong recommendation for vaccination, and facilitate its administration to decreased MO and increase community vaccination rates. One consideration for Oto-HNS providers is whether adding vaccination capabilities would place a significant burden on the clinic to make vaccination fiscally or logistically unviable.…”
Section: Discussionmentioning
confidence: 76%
“…8 Consequently, this new knowledge has not yet fully permeated the medical community, resulting in understandably low awareness of the role of HPV vaccination in head and neck cancer prevention among both patients and providers. 27 Another probable reason for this sex-mediated vaccine discrepancy could be the continuity of care that female patients have with OBGYN providers, who are frequently equipped to administer the HPV vaccine. Finally, targeted marketing campaigns associating the HPV vaccine with protection from cervical cancer, which strongly associates the risk of malignancy with the sexual transmission in females and typically does not address the risk to males, may also have played a role in low vaccination rates among males.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations